The Effect of Processing on Nutrient Utilization of Pigeonpea (Cajanus cajan) Seed Meal and Pigeonpea Seed Meal Based Diets by Pullets - Amaefule, K.U.; Nwagbara, N.N. (International Journal of Poultry Science, 2004)
Two experiments were conducted with fifty-four 9-week old Bovan Nera pullets (24 in experiment 1 and 30 in experiment 2) to determine the effect of processing on the nutrient utilization of pigeonpea seed meal (PSM) and PSM-based diets by pullets. The seeds were processed either as boiled, toasted, soaked or raw (unprocessed). In experiment 2, raw or processed PSM were each included as 10% of a maize-soybean diet. Parameters considered were DM, CP, CF and ether extract utilization of the PSM and that of PSM-based diets. Results showed that in experiment 1, processing significantly increased (P